Perbandingan Efektivitas Latihan Intradialisis dan Profiling Suhu dalam Meningkatkan Mutu Layanan Hemodialisis - Masfuri Masfuri; I Made Kariasa; Leo Ginting (Journal of Telenursing (JOTING), 2023)
This study aims to describe the effectiveness of intradialytic exercises and HD temperature profiling in improving the quality of HD services. The literature search method is based on the compilation of PICO through online database searches on Clinicalkey, Clinicalkey Nursing, ScienceDirect, EBSCO, ProQuest, and Scopus. Journal search results obtained 20,106 articles; after the selection stage, nine reports were obtained for analysis, consisting of 5 RCT articles, one systematic review article, two quasi-experimental articles, and one meta-analysis article. The results showed that HD patients who were routinely given intradialytic exercises would show an increase in HD adequacy achievements, suppress inflammatory reactions, increase albumin and hemoglobin values, reduce the erythropoietin resistance index, increase phosphate clearance, improve the quality of life of HD patients and minimize the risk of both acute and chronic complications. Chronic disease caused by HD. Meanwhile, temperature profiling can reduce the incidence of intradialytic hypotension, pruritus, and fatigue and reduce the severity of Restless Leg Syndrome (RLS) without interfering with the achievement of HD adequacy. This study concludes that intradialytic training and temperature profiling effectively improve the quality of HD services. Keywords: HD Quality, HD Patient Quality of Life, Intradialysis Exercise, Temperature Profiling